Evaluation of exposure to effervescent drugs in a large health check-up population in France: a cross-sectional study. Issue 7 (30th July 2018) - Perrin, Germain; Berdot, Sarah; Thomas, Frédérique; Pannier, Bruno; Danchin, Nicolas; Durieux, Pierre; Sabatier, Brigitte
Abstract : Objectives: The relationship between high dietary sodium intake and hypertension is well established. Some drugs are associated with high-sodium content, particularly effervescent tablets (ETs). Despite a possible cardiovascular risk associated with the use of such drugs, observational data describing exposure to ETs in ambulatory subjects are lacking. This study aims to estimate the prevalence of exposure to ETs and to highlight factors associated with this exposure in a large French health check-up population. Design: This was a cross-sectional study. Setting and participants: Participants were French individuals who underwent medical check-ups at the Investigations Préventives et Cliniques centre between April and June 2017. Results: In total, 1043 subjects were included in the study. The prevalence of exposure to ETs in the last 30 days was 26.9% (95% CI 24.2% to 29.6%). Exposure was frequent (ie, two ETs per week or more in the last 30 days) for 7.3% of subjects. Self-medication was the major source of exposure (93.8%). Paracetamol, aspirin, vitamins and betaine accounted for 95.3% of the ETs used. The factors associated with this exposure by multivariate analysis were: male gender, Overseas French origin, depression and body mass index ≥25 kg/m 2 . A diagnosis of hypertension or treatment with diuretics were not protective factors against exposure to ETs. Conclusion: Exposure to ETs is frequent in the general population, particularly through self-medication. Clinical conditions associated with low-salt requirements were not associated with lower exposure to ETs, suggesting a lack of awareness by practitioners and patients about this iatrogenic issue.